2019
DOI: 10.3390/agronomy9080449
|View full text |Cite
|
Sign up to set email alerts
|

SSR Marker-Assisted Management of Parental Germplasm in Sugarcane (Saccharum spp. hybrids) Breeding Programs

Abstract: Sugarcane (Saccharum spp. hybrids) is an important sugar and bioenergy crop with a high aneuploidy, complex genomes and extreme heterozygosity. A good understanding of genetic diversity and population structure among sugarcane parental lines is a prerequisite for sugarcane improvement through breeding. In order to understand genetic characteristics of parental lines used in sugarcane breeding programs in China, 150 of the most popular accessions were analyzed with 21 fluorescence-labeled simple sequence repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The nucleotide sequence of these SSR primers can be found in Wu et al. (2019). Based on a previous survey, the total number of SSR fragments/alleles produced by these 13 SSR primer pairs was 150 and the potential number of SSR fragments/alleles produced per SSR primer pair varied from 2 to 19 (Pan et al., 2007).…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleotide sequence of these SSR primers can be found in Wu et al. (2019). Based on a previous survey, the total number of SSR fragments/alleles produced by these 13 SSR primer pairs was 150 and the potential number of SSR fragments/alleles produced per SSR primer pair varied from 2 to 19 (Pan et al., 2007).…”
Section: Characteristicsmentioning
confidence: 99%
“…The molecular identity of YT 09-13 was defined with 150 DNA fragments/alleles amplifiable by 13 pairs of microsatellite (simple sequence repeat [SSR]) primers using a highthroughput procedure (Table 7) (Pan, Scheffler, & Richard, 2007). The nucleotide sequence of these SSR primers can be found in Wu et al (2019). Based on a previous survey, the total number of SSR fragments/alleles produced by these 13 SSR primer pairs was 150 and the potential number of SSR fragments/alleles produced per SSR primer pair varied from 2 to 19 (Pan et al, 2007).…”
Section: Botanical and Molecular Descriptorsmentioning
confidence: 99%
“…Marker-assisted selection was applied in four studies for (1) the selection of parental germplasm in sugarcane breeding programs [18], (2) improving blast resistance and salt tolerance in rice [19], (3) the selection of the pollination constant non-astringent (PCNA) type in Spanish germplasms of persimmon [20], and (4) the selection of resistance to plum pox virus (PPV) in apricot by allele-specific PCR [21]. Wu et al [18] identified two groups among the 150 most widely used sugarcane parental clones. Based on these results, the authors could identify the most appropriate cultivars to broaden the genetic base of breeding germplasm.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Marker-assisted selection was applied in four studies for (1) the selection of parental germplasm in sugarcane breeding programs [18], (2) improving blast resistance and salt tolerance in rice [19], (3) the selection of the pollination constant non-astringent (PCNA) type in Spanish germplasms of persimmon [20], and (4) the selection of resistance to plum pox virus (PPV) in apricot by allele-specific PCR [21]. Wu et al [18] identified two groups among the 150 most widely used sugarcane parental clones. Based on these results, the authors could identify the most appropriate cultivars to broaden the genetic base of breeding germplasm.…”
Section: Overview Of the Special Issuementioning
confidence: 99%